Subgroups in the treatment of nasal polyposis with dupilumab: a retrospective study - Bertlich, Mattis Ralf Otfried; Freytag, Saskia; Dombrowski, Tobias; Jurmeister, Philipp; Spiegel, Jennifer Lee; Bertlich, Ines; Ihler, Friedrich; Weiss, Bernhard G.; Haubner, Frank; Gröger, Moritz (Medicine, 2022)
Dupilumab has been shown to be safe and effective in treating chronic rhinosinusitis with polyposis (CRSwNP). There is to this date no published data whether subgroups like patients with aspirin exacerbated respiratory disease (AERD), increased histologic eosinophilia or elevated blood eosinophil or IgE-levels benefit greater from dupilumab therapy. Moreover, there is no data comparing the efficacy of functional endoscopic sinus surgery (FESS) with dupilumab therapy. We conducted a retrospective chart review of all patients that were treated at a tertiary referral center for CRswNP with dupilumab. We also contacted the patients with a questionnaire to evaluate the efficacy of previous surgeries and dupilumab therapy by visual analogue scale (VAS) and the glasgow benefit inventory (GBI) as well as report on side effects. ...